A bridge too far [videorecording (DVD)] - Attenborough, Richard; Bogarde, Dirk, 1921-1999; Caan, James; Caine, Michael; Connery, Sean; Ryan, Cornelius (MGM Home Entertainment, 1998)
In September 1944, flush with success after the Normandy Invasion, the Allies launched Operation Market Garden, an Allied airdrop behind German lines in Holland intended to put an early end to World War II by invading Germany and smashing the Reich's war plants, but which resulted in the disastrous Battle of Arnhem.